PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA - Yulita, Elsi; Adripen, Adripen; Kurnia, Lely (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research was to know mathematics communication ability of students by applaying cooperative learning model type TTW at class XI.IPS SMAN 1 Sungayang. The study was quasi eksperimental research with the draft of research was Randomized Control Group Only Design. The subject of this research obtained from the final test. The hypothesis of this research was tested by MIINITAB program named t-test one way. The results showed a difference in mean value, variance and standard deviation in the second grade sample. From the result of t-test, research obtained that p-value 0.00, so the hypothesis of this research is accepted at significant standard Î± = 0.05. So, concluded that the mathematics communication ability of students was by applaying of cooperative learning model type TTW higher than students in conventional leraning.Keywords:Â Cooperative Learning, Think Talk Write (TTW), Mathematics Communication Ability